Coexistence of Peripheral Spondyloarthritis and Familial Adenomatous Polyposis: A Rare Case Report with Treatment Contradictions and Review of the Literature. - Urkmez, Berna; Kepekci, Muge; Posul, Sevde Ozer; Rezvani, Aylin (My University, 2017)
The coexistence of familial adenomatous polyposis and spondyloarthritis is rarely defined in literature. The primary aim of this presentation is to report a development of peripheral arthritis in 3 years following colon surgery with the diagnosis of familial adenomatous polyposis (FAP). The secondary aim is to discuss the challenge of in treatment of refractory arthritis, which needs to be treated with biologics. However, it is not yet known well about their safety on patients who have risks for cancer development.

A 25-year-old female patient was admitted to the rheumotology outpatient clinic. The patient had undergone total colectomy and ileoanal anastomosis because of FAP three years ago. On her physical examination, there was arthritis on her left ankle and enthesitis on both Achilles tendons.

This case report presents a 25-year-old female patient with Ankylosing spondylitis (AS) and FAP whose treatment with biologics is critical due to the risk of cancer development due FAP. Although the potential risk of development of malignancies with TNF-blocking therapy seems to be no more than TNF-naïve patients and general population. But the safety of these drugs on patients with risks for cancer development is still unknown.
Keywords: Spondyloarthtritis; biologics; disease modifying anti-rheumatic drugs; familial adenomatous polyposis; nonsteroid anti-inflammatory drugs